IMPLEMENTATION OF THE POLICY ON THE USE OF THE MERDEKA FIELD IN SUKABUMI CITY - Shima Claudia; Rizki Hegia Sampurna; Dian Purwanti (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
Merdeka field is a public green open space that serves the functions as stipulated in Sukabumi Mayor Regulation No. 4 of 2017, namely as a venue for ceremonies, sports, education, and other activities of the Sukabumi City Government. However, in practice, there has been a shift in function, with the emergence of various activities, including community activities and informal economic activities that are not subject to regulation. This situation indicates a gap between the established policies and their implementation on the ground. This study aims to analyze the implementation of policies regarding the use of the Merdeka field in Sukabumi City, as well as the factors influencing this implementation. The method employed is a descriptive qualitative approach, utilizing data collection techniques that include observation, interviews, and documentation. The theoretical framework employed is Merilee S. Grindle's policy implementation model, which encompasses both policy content and the context within which policy is implemented. The results of the study show that in terms of policy content, the intended benefits have not been optimally realized, there is a mismatch between the policy and conditions on the ground, low community involvement in decision-making, ineffective implementation by technical agencies, and resource constraints. Meanwhile, in terms of the context of policy, there is a diversity of interests among actors, weak implementation strategies, and low levels of community compliance due to minimal socialization and enforcement of regulations. This study recommends increasing massive and continuous dissemination of information regarding the policy on the use of the Merdeka field to the public; strengthening the capacity and number of field officers so that supervision and management of the Merdeka field can run optimally; and providing alternative economic zones for street vendors to maintain the function of public space by regulations.